Elastic Constants by Resonant Ultrasound Spectroscopy – Application to Thermoelectrics and Aluminum Alloys - Benedikt Klobes (Scientific Journal of Gdynia Maritime University, 2019)
Resonant ultrasound spectroscopy is a non-destructive technique for determining the elastic constants of a material. In the context of thermoelectric materials, elastic constants can be used to investigate the speed of sound and, thus, the lattice thermal conductivity of a substance. For Mg2Si-Mg2Sn solid solutions, a possible connection between shear modulus and band convergence can be assumed in that way. Moreover, the rather low speed of sound in this system points towards a high contribution of optical phonons to thermal conductivity. Additionally, significant resonance frequency shifts are observed during natural aging of technical Al-Cu-Mg and Al-Mg-Si alloys, which are proposed to assist investigation of the early stages of clustering in the future.